(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
Meatballs are widely liked and very popular food in Indonesia because in terms of prices, meatballs are feasible by all people. This study aims to obtain a recipe for tilapia fish meatballs with taro flour substitution. Methods and research design using True Experimental Design. An experimental method was carried out by using the quantitative descriptive analysis (QDA) test from 5 expert panelist and 30 untrained panelists to demonstrate the similarity of tilapia fish meatballs compare to the reference product. The results showed that the trial of tilapia fish ball product with taro flour substitution was carried out 2 times to get the right formula. The first experiment used 12.5% taro flour substitution, while the second was 10%. A standard recipe for tilapia fish meatballs with taro flour substitution formulated by 75% of tilapia fillet, 10% of taro flour, 15% of tapioca flour, 22.5% of chicken egg (white), 22.5% of ice cubes, 15% of onion, 1.5%, of garlic, 2.5% of salt, and 1% of ground pepper. The results of the QDA test by 5 expert panelists, showed that product characteristics were having a fairly smooth and uniform shape, dark white fish meatball color, strong fish aroma, strong fish taste. Taro flour taste does not interfere with the taste of fish balls, while the seasoning was quite strong with the texture was chewy and not hard. The acceptability test demonstrated that from 30 untrained panelists, the recipe could be accepted positively with the appearance, color, taste, and texture categories were very favorable, while the aroma was favored by the panelists as a processed fish ball product.